Engenharia de aplicação para sistemas embarcados : transformando especificações SysML em Simulink - Fragal, Vanderson Hafemann (2013)
The evolution of hardware platforms has transferred a great amount of functionality to embedded software, thus increasing its complexity. Model Driven Engineering (MDE) and Software Product Line (PL) can enhance the development of embedded systems by means of using different specification languages according to the abstraction levels and and ways to manage variability across development. The SyMPLES approach supports the conception of SysML-based PLs. It includes two SysML extensions, created by means of the UML profiling mechanism both to express PL variability concepts and to associate SysML blocks to the main classes of functional blocks. SyMPLES was initially created with focus on domain engineering activity of PL, since the models generated in the application engineering activity are not refined. This dissertation presents one transformation process from SysML to Simulink models that is intended to supplement the SyMPLES approach. SysML models created in the PL application engineering activity from SyMPLES are used to create functional blocks and state machines. An application example was developed for one subsystem of an autopilot board used in Unmanned Aerial Vehicles, named Yapa 2 of Paparazzi project, which was studied into the context of National Institute of Science and Technology for Safety Critical Embedded Systems (INCT-SEC). The results show that SysML configured models can be transformed in order to represent the system with functional blocks, which facilitates the generation of code.